Kepribadian Big Five Pada Emerging Adulthood: Sebuah Tinjauan Literatur Sistematis - Sholihah, Hanifah (Affection: Journal of Psychology And Counseling, 2024)
Individuals who have entered adulthood will definitely experience personality changes throughout their life span. This study is a literature review with a systematic approach that aims to explore the big five personalities in emerging adulthood. The results of this study are that the big five's personality can change throughout the life span. This is because a person's personality can be influenced by internal and external factors. Internal factors within oneself, such as the big five personality traits (extraversion, openness, emotional stability, conscientiousness, agreeableness), while external factors, such as environmental influences and life events. The role of mindset is very important in moderating the big five personality, so this study can show that the dimensions of extraversion, openness, agreeableness show a significant increase in emerging adulthood, while agreeableness and emotional stability do not show a significant increase in emerging adulthood.